Utilizing the Four Square Writing Method to Improve Students' Ability in Writing Narrative Text - Utami, Evie Tri; Rohbiah, Tatu Siti; Kheryadi (English Education, Linguistics, and Literature Journal, 2024)
This research aims to investigate the impact of the Four Square Writing method on student achievement in writing narrative texts. Additionally, it analyzes factors that could influence the students‘ achievement in writing narrative text. The study employs a quasi-experimental approach with two classes, an experimental class (Class X-2) and a control class (Class X-3). The primary data collection involves pre-tests and post-tests, where students are assessed in writing narrative stories. The assessment criteria are based on Jacob et al.'s theory, encompassing content, organization, grammar, language use, and mechanics. In addition, the questionnaire is also involved in this research to know the factors of writing narrative text achievement. The findings of this research indicate a significant positive effect of using the Four Square Writing method in teaching narrative text writing to tenth-grade students at SMA Al-Fath in Cilegon City. The statistical analysis reveals that t0 : tt = 4.632, which is greater than the critical value of at a 5% and 1% significance level. The factors influencing students' achievement in writing narrative text in sequental order are the teaching method, motivation, students' personality and interests, teaching materials, teacher feedback, cognitive ability, media use, and the classroom environment. This research helps students to improve their ability to structure and organize narrative writing effectively and enhances their understanding of grammar and proper language use in writing.